Customer Discovery of Biofertilizer Business (A Lesson From PT PHN Experience) - Yeni Marlina; Idqan Fahmi; Arif Satria (Jurnal Manajemen & Agribisnis, 2018)
Demand for agricultural products in Indonesia increases in response to Indonesia's high population growth. With more limited agricultural land, agricultural productivity can be increased by the addition of fertilizer. Biofertilizer is currently popular fertilizer and can become a solution to increase productivity of agricultural products in limited land. PT PHN is a new company established in 2015 and produces biofertilizer under the brand XYZ . This research was conducted to analyze consumer perception of biofertilizer and XYZ fertilizer. The company tries to understand customer’s problems and provides solutions with customer development model (CDM) method. Understanding and solution to the problem were then used as revision of the company's business model with business model canvas (BMC) approach. Primary and secondary data were used in this research. Primary data were obtained by observation and interview using several respondents. Secondary data were obtained from PT PHN staffs, BPS, and other sources related to this research. The results show that consumers do not have enough understanding about biofertilizer. XYZ fertilizer improves agricultural productivity but has some obstacles in its use. The business model of PT PHN is updated with some additions and subtractions by considering the CDM results.Keywords: BMC, business model, CDM, strategy, customer discovery